Consortium for violence prevention research, leadership training, and implementation for excellence (CONVERGE): a protocol to train science leaders in gender-based-violence and violence-against-children research for impact - Kathryn M. Yount; Dawn Comeau; Sarah C. Blake; Jessica Sales; Michael Sacks; Hannah Nicol; Irina Bergenfeld; Ameeta S. Kalokhe; Aryeh D. Stein; Daniel J. Whitaker; Dominic Parrott; Hoang Thi Hai Van (Frontiers Media S.A., 2023)
BackgroundGender-based violence (GBV) and violence against children (VAC) are two prevalent and highly interconnected global health challenges, yet data and research capacities to study these forms of violence and to generate evidence-based policies and programs remain limited. To address critical shortages in research capacity in Vietnam and to establish a model for other Low- and Middle-Income Countries (LMICs), we are establishing CONVERGE-the Consortium for Violence Prevention Research, Implementation, and Leadership Training for Excellence.MethodsBased on a needs assessment with partners in Vietnam, CONVERGE will provide a comprehensive research training program supporting 15 long-term, postdoctoral trainees with multi-disciplinary research training in GBV and VAC. We also will offer in-country trainings and short-courses to 40 short-term mid-career academic trainees and 60 short-term practitioner/stakeholder trainees over 5  years to build productive GBV and VAC academic, scientific, and practitioner networks. The CONVERGE training program has four components: (1) 14 h of virtual/in-person annual mentorship training to prepare research mentors and to create a pipeline of future mentors in Vietnam; (2) a one-month intensive research training for long-term postdoctoral fellows at Emory University; (3) a structured 17-month, in-country mentored research project for long-term trainees that results in a peer-reviewed manuscript and a subsequent grant submission; and, (4) week-long in-country intensive translational trainings on implementation science, advanced topics in leadership, and advanced topics in science dissemination. Opportunities for on-going virtual training and professional networking will be provided for CONVERGE trainees and mentors in Vietnam with other trainees and mentors of D43s focused on injury/violence prevention, D43s housed at Emory, and D43s with other institutions in Southeast Asia. To assess the reach, implementation, fidelity, and effectiveness of these four components, we will implement a rigorous, mixed-methods, multi-level evaluation strategy using process and outcome measures. Findings from the evaluation will be used to refine program components for future trainee and mentor cohorts and to assess long-term program impact.DiscussionLed by Emory University in the US and Hanoi Medical University in Vietnam, CONVERGE represents leading institutions and experts from around the world, with a goal of providing mentorship opportunities for early-career scientists with an interest in violence prevention.